Effect of W concentration in the organized Ti-W alloy oxide nanotubes array on the photoelectrocatalytic properties and its application in the removal of endocrine disruptors using real water matrix - Almeida, Juliana de [UNESP]; Kaminagakura, Verena Mandorino; Felez, Marissol Rodrigues; Leon, Carlos Ponce de; Bertazzoli, Rodnei [UNESP]; Rodrigues, Christiane de Arruda [UNESP] (Elsevier, 2022)
To evaluate the tungsten content on the photoelectrocatalytic properties of self-organized nanotubes grown by anodization on Ti-xW (wt%) alloys, where x is 0.5, 2.5 or 5.0, this work investigated the phase transformation of TiO2, the tungsten oxidation states in the oxide layers and their photoelectrocatalytic performance in the degradation of estrone (E1) and 17α-ethinylestradiol (EE2). These films were employed in photocatalytic and photoelectrocatalytic removals of hormones from synthetic and real water matrices. In synthetic water, E1 and EE2 removals, reached efficiencies of 92% and 71%, respectively, after 2 min under UV-Vis photoelectrocatalysis using NT/Ti-5.0W as catalyst. About 30 times longer was needed to degrade 77% of both hormones from the real water matrix due to the presence of other high organic charge. The high performance of the NT/Ti-5.0W was associated with the combination of doping (W-doped TiO2) and WO3 (W6+) heterojunction. However, this electrode had its stability compromised under long degradation times, mainly under visible light, due to a WO3 leaching process. As for NT/Ti-0.5W, the substitutional W-doped TiO2 contributed to its greater stability and efficiency for a long time. The low performance of NT/Ti-2.5W was justified by high density of oxygen vacancy and unfavorable position of its adsorption bands.
Keywords: Hormones; Nanotubes; Photoelectrocatalytic degradation; Real water matrix; Ti-W alloy; Tungsten oxide